2023
DOI: 10.1097/01.hc9.0000897224.68874.de
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of patients with COVID-19 and chronic liver disease: US multicenter COLD study

Abstract: Background: COVID-19 is associated with higher morbidity and mortality in patients with chronic liver diseases (CLDs). However, our understanding of the long-term outcomes of COVID-19 in patients with CLD is limited. Methods: We conducted a multicenter, observational cohort study of adult patients with CLD who were diagnosed with COVID-19 before May 30, 2020, to determine long-term clinical outcomes. We used a control group of patients with CLD confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A 1-year long follow-up study, involving patients with CLD with a history of COVID-19 and a propensity matched control group without a history, reported a significant increase in all-cause mortality (8.0% vs 2.0%) and higher rates of hospitalisation (34% vs 21%) in the patients who had had COVID. 81 Comparable minorities of the patients had compensated (17.2%) and decompensated (5.5%) cirrhosis at baseline; cirrhosis was, however, an independent predictors of overall survival and hospitalisation. Seventy percent of the patients with a history of COVID-19 had received at least one dose of a COVID-19 vaccine.…”
Section: Longer Term Outcomesmentioning
confidence: 87%
See 3 more Smart Citations
“…A 1-year long follow-up study, involving patients with CLD with a history of COVID-19 and a propensity matched control group without a history, reported a significant increase in all-cause mortality (8.0% vs 2.0%) and higher rates of hospitalisation (34% vs 21%) in the patients who had had COVID. 81 Comparable minorities of the patients had compensated (17.2%) and decompensated (5.5%) cirrhosis at baseline; cirrhosis was, however, an independent predictors of overall survival and hospitalisation. Seventy percent of the patients with a history of COVID-19 had received at least one dose of a COVID-19 vaccine.…”
Section: Longer Term Outcomesmentioning
confidence: 87%
“…Seventy percent of the patients with a history of COVID-19 had received at least one dose of a COVID-19 vaccine. 81 People infected with COVID-19 can experience long-lasting debilitating symptoms. The term "long-COVID-19" is used to describe "physical, medical, and cognitive symptom lasting for at least 2 months following COVID-19 infection, for which there is no other explanation".…”
Section: Covid-19 Vaccination and Liver Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, when patients have underlying chronic comorbidities, the outcomes would be worse. A recent large study of adult patients with chronic liver disease who were diagnosed with COVID-19 before May 2020, found that symptoms consistent with long-COVID-19 were present in 30% of patients with chronic liver disease [ 44 ]. Different studies have also demonstrated significant and long-lasting neurological manifestations [ 45 , 46 ].…”
mentioning
confidence: 99%